2006
DOI: 10.1007/s00221-006-0628-y
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of 1 Hz rTMS over the cerebellum on motor cortex excitability

Abstract: Clinical observations and data from animal experiments point to a physiological facilitatory influence of the deep cerebellar structures on the motor system through the cerebello-thalamo-cortical pathways. The aim of the present study was to explore the long-term effects of low-frequency (1 Hz) repetitive transcranial magnetic stimulation (rTMS) over the cerebellum on short intracortical inhibition (SICI) and facilitation (ICF) of the motor cortex in normal subjects. Eight healthy subjects (mean age 26.9 +/- 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 33 publications
7
92
2
2
Order By: Relevance
“…tSMS over the cerebellum, during which the stimulus intensity may have been 0.1-0.2 Tesla, did not affect the excitability of the contralateral motor cortex, and the duration of the aftereffect was very short in this study. On the other hand, delivering 1-Hz rTMS with an intensity of approximately 1 Tesla to the contralateral cerebellum can inhibit the excitability of the contralateral motor cortex and the effect can reportedly continue for over 20 min (Fierro et al, 2007). On the basis of these findings, we speculate that the ability of the stimulation to affect the excitability of the contralateral motor cortex, as well as the duration of the effect, may be related to the type of magnetic field, for instance, a static or varying magnetic field, or the strength of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tSMS over the cerebellum, during which the stimulus intensity may have been 0.1-0.2 Tesla, did not affect the excitability of the contralateral motor cortex, and the duration of the aftereffect was very short in this study. On the other hand, delivering 1-Hz rTMS with an intensity of approximately 1 Tesla to the contralateral cerebellum can inhibit the excitability of the contralateral motor cortex and the effect can reportedly continue for over 20 min (Fierro et al, 2007). On the basis of these findings, we speculate that the ability of the stimulation to affect the excitability of the contralateral motor cortex, as well as the duration of the effect, may be related to the type of magnetic field, for instance, a static or varying magnetic field, or the strength of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we tested this hypothesis by examining the CBI before and after applying tSMS over the cerebellum. Previous studies have shown that rTMS over the cerebellum modulates CBI (Celnik, 2015) and the excitability of the contralateral M1 (Oliveri et al, 2005;Fierro et al, 2007;Popa et al, 2010). Thus, if the excitability of the cerebellum is changed by tSMS, the excitability of the contralateral M1 may be modulated by applying tSMS over the cerebellum.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the NIBS to the cerebellum modulates cerebellar excitability [98,[129][130][131], motor function [132,133], and motor learning [32,[134][135][136][137][138] in healthy population. In patients with cerebellar ataxia, some previous studies reported about the effect of tDCS to the cerebellum on motor function [131,[139][140][141].…”
Section: Noninvasive Brain Stimulation (Nibs)mentioning
confidence: 99%
“…The effect lasted for up to 30 min afterwards. Fierro et al 43 (8 healthy subjects) explored the long-term effects of low frequency rTMS over the right cerebellum with 900 pulses at 1 Hz. Before and after cerebellar rTMS, SICI and ICF were assessed in the left motor cortex by a paired pulse paradigm (ISI 2-15 ms).…”
Section: C) Tms Of Cerebellum As a Conditioning Stimulationmentioning
confidence: 99%